A call for conscious “anti-preparation” to motherhood - Bujold, Audrey; Vallée-Ouimet, Sandrine (Aporia)

(untitled) (University of Ottawa, 2024)
Our privileged position as doctoral students and mothers allows for a critical look at this issue that leads us to propose a form of “anti-preparation” to motherhood, in the sense that women should be called upon to deconstruct the constraining beliefs surrounding motherhood rather than accumulate new knowledge that is sometimes contradictory, often useless, and particularly anxiety-provoking. This is not a call to ignorance, but it does encourage us to temper our consumption of knowledge that can generate beliefs that erode and, above all, invisibilize women’s intrinsic strengths. While some of information surrounding motherhood is essential to know, we suggest that more attention must be devoted to empowering mothers and challenging dominant norms that ultimately don’t always serve them. In short, this plea seeks to challenge the authoritarian function of medicalized knowledge embedded in capitalist and patriarchal norms of motherhood, which work to minimize the intrinsic strengths of mothers. Our intention is not to promote an inclusive view that rests on the commercialization of motherhood, but rather an anti-oppressive approach that legitimizes both the intrinsic strengths of mothers and their facilitating beliefs, whether medicalized or tacit.